KECEPATAN EMAS DAN EURO PADA STABILITAS BARU PASCA SHOCK ECONOMIC - muhajirin, Muhajirin (At-Tauzi : Jurnal Ekonomi Islam, 2022)
After the abandonment of gold currency and gold-standard currency in 1914, there was a great depression in 1930 and it boiled down to the Bretton Woods agreement which agreed that; the money minted should be gold-based. However, in 1971 this agreement was violated by Nixon the American president with USD as fiat money. Since then until now, no country has used gold currency or with the gold standard, and there have been several financial and economic crises, among them in 1997, 2008, 2015 and 2018. This study aims to test the speed of gold (commodity currency) to return to a new stability point after the occurrence of an economic shock compared to the ability of the Euro as a (union currency) of EU countries through the Global CPI indicator. This study used secondary data from Fred Economic Data, Economic Research, Federal Reserve Bank of ST. Louis, The global economy.com, economic indicators for over 200 countries, and OECD.org. Using the Vector Error Correction Model (VECM), Impulse Response Function and Variance Decomposition, this study shows that gold is a more stable commodity (money) (fast to a new equilibrium point) when compared to the Euro (union currency) after the shock economy.